2004
DOI: 10.1007/s11940-004-0039-y
|View full text |Cite
|
Sign up to set email alerts
|

Acute hearing loss

Abstract: Acute hearing loss (AHL) is a medical urgency. The management of patients presenting with sudden deafness involves detecting the causal mechanism and administering emergency therapeutic drugs to restore hearing by minimizing the period of cellular ischemia to the inner ear. Acute management of AHL consists of administering a 10-day course of high-dose corticosteroids (prednisone 60 to 80 mg) until a cause can be established. Magnetic resonance imaging with gadolinium is indicated, with a study dedicated to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 47 publications
1
12
0
1
Order By: Relevance
“…Overall, our patients had a recovery rate of 81%, which is above the spontaneous recovery rate (40-69%) reported for idiopathic sudden sensorineural hearing loss [14,16], but is similar to the recovery rate (61-89%) of idiopathic sudden sensorineural hearing loss after steroid treatment [11][12][13]. Like previous studies [15,17,27], we found that patients with profound hearing loss had poorer outcome than the patients with less than profound hearing loss. However, these comparisons must be made with caution since idiopathic sudden sensorineural hearing loss likely represents a mixture of etiologies.…”
Section: Long-term Outcome Of Sudden Deafnesssupporting
confidence: 80%
See 1 more Smart Citation
“…Overall, our patients had a recovery rate of 81%, which is above the spontaneous recovery rate (40-69%) reported for idiopathic sudden sensorineural hearing loss [14,16], but is similar to the recovery rate (61-89%) of idiopathic sudden sensorineural hearing loss after steroid treatment [11][12][13]. Like previous studies [15,17,27], we found that patients with profound hearing loss had poorer outcome than the patients with less than profound hearing loss. However, these comparisons must be made with caution since idiopathic sudden sensorineural hearing loss likely represents a mixture of etiologies.…”
Section: Long-term Outcome Of Sudden Deafnesssupporting
confidence: 80%
“…AICA infarction was unilateral in the both groups. Third, isolated caudal cerebellar infarcts (n=4, patients [24][25][26][27] in the distribution of the medial branch of the PICA. Fourth, isolated brainstem infarcts (n=2) involving the paramedian pons (patient 28) and the lower midbrain and upper dorsolateral pontine tegmentum (patient 29).…”
Section: Topography Of Infarcts Associated With Sudden Deafnessmentioning
confidence: 99%
“…In various studies the time between onset of symptoms and presentation has been observed to be a prognostic factor [5,23]. The question is whether a sample of patients presenting early after the onset of symptoms would not have a better outcome regardless of treatment chosen than a sample of patients presenting later.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing hearing losses in low, middle and high frequencies, low-tone ISHLs seem to have the best prognosis, with an expected spontaneous recovery rate of 80% [4]. Other prognostic factors are age, presence or absence of vestibular symptoms, the time between the onset of symptoms and the start of therapy, previous otological history and presence of risk factors such as hyperlipoproteinemia, obesity, hypertonus, and stress [5].…”
Section: Idiopathic Sudden Hearing Lossmentioning
confidence: 99%
“…Comparing hearing losses in low, middle, and high frequencies, low-tone ISHLs seem to have the best prognosis, with an expected spontaneous recovery rate of 80% [5]. Other prognostic factors are age, presence or absence of vestibular symptoms, the time between the onset of symptoms and the start of therapy, previous otological history, and the presence of risk factors such as hyperlipoproteinemia, obesity, hypertonia, and stress [6].…”
mentioning
confidence: 99%